Eurocity Chaves-Verín, cross-border tourism experience in the Iberian Peninsula - Liberato, Dália (2019)
The Eurocity Chaves-Verín, as an European Grouping of Territorial Cooperation (EGTC), will be the central region to address in this work, focusing particularly on the issue of good practices taken into account in the existing cooperation link in these two cross-border regions, regarding the Thermal and Water Route Verín-Chaves-Vidago, as a leading proposal that fits and complements other offerings, creating competitiveness prospects for the destination, based on the quality offer, solely in endogenous resources, diversity of complementary tourism products, resulting in advantages for the stakeholders of the destination by extending the average stay and reducing seasonality. The results of the research show that the appreciation of the complementarity of the products made available to tourists, can effectively culminate in the increasing competitiveness of the destination, if the partnerships are valued and concretized, and if the stakeholders demonstrate openness regarding the proposals of the EGTC, concerning the valorisation, planning and promotion of tourism products arising from both regions.